Inter-rater reliability of TT-TG distance is good and does not vary based on preselected versus independent slice selection on MRI. Issue 6 (13th October 2019) - Beals, Corey; Flanigan, David C; Peters, Nicholas; Kim, Walter; Early, Nicholas; Shemory, Scott; Vasileff, William K; Magnussen, Robert A
Abstract : Objectives: Patellar instability is a frequent cause of knee dysfunction in young, active patients. Tibial tubercle–trochlear groove (TT-TG) distance, trochlear morphology (trochlear depth and sulcus angle) and patellar height are felt to contribute to patellar instability and may influence treatment. These measurements are frequently performed on MRI images. We hypothesised that inter-rater reliability of measures would be good and that inter-rater variation is driven primarily by slice selection. Methods: Twenty-six patients with at least one documented episode of patellar instability confirmed by MRI were identified. Six raters reviewed MRI images from each patient. Each rater measured and recorded TT-TG distance, trochlear depth and sulcus angle, and patellotrochlear index (PTI) for each patient and the slices used for the measurements. Each rater repeated the measurement using preselected slices. Inter-rater reliability was calculated by intraclass correlations (ICCs) for slice selection and for TT-TG distance, trochlear morphology measures and PTI with both independently selected and preselected slices. Statistically significant differences (p<0.05) in ICC based on slice selection were defined as values without overlap of their 95% CIs. Results: Inter-rater reliability was excellent for tibial (ICC=0.93) axial slice selection and sagittal slice selection (ICC=0.94), and good for femoral (ICC=0.88) axial slice selection. Using independent slice selection, inter-rater reliability was good for TT-TG distance (ICC=0.79) and fair for trochlear depth (ICC=0.57), sulcus angle (ICC=0.57) and PTI (ICC=0.71). When preselected slices were used, inter-rater reliability was good for TT-TG distance (ICC=0.85), sulcus angle (ICC=0.83) and PTI (ICC=0.77) and fair for trochlear depth (ICC=0.68). Only sulcus angle demonstrated a significant (p<0.05) improvement in inter-rater reliability with the use of preselected slices. Discussion and conclusion: Inter-rater reliability of TT-TG distance is good and does not vary based on preselected versus independent slice selection on MRI. Inter-rater reliability of trochlear morphology measures based on axial MRI slices and PTI is fair. Inter-rater variation can be reduced (particularly in the case of sulcus angle) through agreement on slice selection. Level of evidence: Level III, diagnostic.